Вплив стеарату натрію в комбінації з кадмієм на стан перекисного окиснення ліпідів в організмі піддослідних тварин = Influence of sodium stearate combined with cadmium on lipid peroxidation in experimental animals - Lototska, O. V.; Lototskyy, V. V.; Buhel, O. P. (Journal of Education, Health and Sport, 2015)
Lototska O V, Lototskyy V V, Buhel O P. Вплив стеарату натрію в комбінації з кадмієм на стан перекисного окиснення ліпідів в організмі піддослідних тварин = Influence of sodium stearate combined with cadmium on lipid peroxidation in experimental animals. Journal of Education, Health and Sport. 2015;5(5):117-124. ISSN 2391-8306. DOI 10.5281/zenodo.17456 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A117-124 https://pbn.nauka.gov.pl/works/559173 http://dx.doi.org/10.5281/zenodo.17456 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. УДК 616-092.9-099:546.32:54-145.2-06:612.015.31 ВПЛИВ СТЕАРАТУ НАТРІЮ В КОМБІНАЦІЇ З КАДМІЄМ НА СТАН ПЕРЕКИСНОГО ОКИСНЕННЯ ЛІПІДІВ В ОРГАНІЗМІ ПІДДОСЛІДНИХ ТВАРИН INFLUENCE OF SODIUM STEARATE COMBINED WITH CADMIUM ON LIPID PEROXIDATION IN EXPERIMENTAL ANIMALS О. В. Лотоцька, В. В. Лотоцький, О. П. Бугель O V Lototska, V V Lototskyy, O P Buhel ДВНЗ «Тернопільський державний медичний університет імені І.Я. Горбачевського МОЗ України» SHEI "I.Ya. Horbachevsky Ternopil State Medical University of MPH of Ukraine" Summary The effect of drinking water with different contents of sodium stearate in combination with cadmium on lipid peroxidation and antioxidant protection in rats. It was found that prolonged receiving of water solution with sodium stearate 125.0 and 62.5 mg/dm3 negative effect on experimental animals as a result of the activation of lipid peroxidation and oppression of antioxidant system. The combination of sodium stearate and cadmium, even after a single administration of the latter, increases the toxic effect of stearate - the evidenced is a marked change in levels of indicators. Key word: lipid peroxidation, antioxidant protection, sodium stearate, cadmium, drinking water, white rats. Резюме Вивчено вплив питної води з різним вмістом стеарата натрію в комбінації з кадмієм на перекисне окислення ліпідів та стан антиоксидантного захисту в організмі щурів. Встановлено, що тривале вживання піддослідними тваринами водного розчину з концентраціями стеарата натрію 125,0 і 62,5/дм3 негативно впливає на організм піддослідних тварин внаслідок активації процесів перекисного окислення ліпідів і пригнічення антиоксидантної системи. Комбінація стеарата натрію з кадмієм навіть після одноразового введення останнього підсилює токсичну дію стеарата, про що свідчило більш виражена зміни показників. Ключові слова: перекисне окислення ліпідів, антиоксидантний захист, стеарат натрію, кадмій, питна вода, білі щури.